Kecendrungan Warna Tanah dan Status Bahan Organik Pada Lahan Pertanian yang Mengalami Penutupan Awan Rendah Berbasis Peta Terra Modis di Pulau Lombok - Dewanti Ayu Fitriani; Mahrup Mahrup; Ismail Yasin; Lalu Arifin Aria Bakti (Department of Soil Science, Faculty of Agriculture, University of Mataram, 2022)
Research has been carried out on the tendency of soil color and the status of organic matter on agricultural land with low cloud cover based on the fashionable terra map on the island of Lombok. The purpose of this study was to determine the tendency of soil color and the status of organic matter on agricultural land which is experiencing low cloud cover continuously based on the Terra Modis map on Lombok Island. This study uses a descriptive method, the data used is data obtained from direct sampling on the land (then analyzed the samples in the laboratory), cloud cover data obtained from the Terra satellite, and Rupa Bumi Indonesia (RBI) map data. can be obtained from the NTB Regional Planning and Development Agency (BAPPEDA). The results of this study indicate that on the island of Lombok, low cloud cover on dry land typology with Inceptisols soil type did not cause changes in the color of the main base matrix (hue) of the soil, brightness (chroma), except for different color saturation variables (value). amounting to 0.5 units, where the land covered by clouds tends to be darker than the land without cloud cover and there is an initial sign, that the organic matter which has no significant difference in levels in the two land conditions, shows a soil color response of 7.5 YR 2.5 / 2 is darker on cloud-covered land than is resistant without colored cover. 2.5 YR 3/2.